Recovery of the physiological status in professional basketball players using NESA neuromodulation treatment during different types of microcycles in season: A preliminary randomized clinical trial - García, F.; Fernández, D.; Vázquez-Guerrero, J.; Font, R.; Moreno-Planas, B.; Álamo-Arce, D.; Medina-Ramírez, R.; Mallol-Soler, M. (Frontiers in Physiology, 2022)
The purpose of the study was to describe and compare recovery status after official basketball competition in players who underwent NESA neuromodulation treatment (NNT) in weeks with one or two matches. The recovery parameters of 12 professional male basketball players (mean ± SD, age: 20.6 ± 2.7 yr.; height: 197.8 ± 11.7 cm; and body mass: 89.0 ± 21.2 kg) that competed in the LEB Plata (Spanish third division) were monitored two days after match-play over six weeks, and included: 1) the Hooper Test, which combines four subjective variables (Sleep, Stress, Fatigue and Soreness); 2) common biochemical markers (e.g., testosterone and cortisol); and 3) sleep variables extracted from Oura Ring (lowest heart rate [HR], average HR, HR variability, sleep duration, awake time and onset latency). Players that completed NNT presented different results to the control group in sleep data, the lowest HR (p <0.001), average HR (p <0.001) and total awake time (p = 0.04) were significantly reduced in the NNT group. On the contrary, the control group presented better values in the subjective Hooper Test than the NNT group, although only stress presented significant differences (Control 2.5 ± 1.2 vs NNT cost or 3.2 ± 0.9; p = 0.01). In addition to the differences between the NNT and control group, there were no significant differences in recovery parameters between weeks with one or two matches. In conclusion, the results suggest that players that underwent NNT tended to improve their sleep quality, although their biochemical markers and wellness status remained similar to those of the control group. Furthermore, the fact that no significant differences were found between weeks with 1 or 2 matches could help basketball professionals to determine that a congested schedule does not seem to negatively alter recovery status. Clinical trial registered in www.clinicaltrial.gov (registration number NCT0493918)